If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9y + -8y + -4 = 5 Reorder the terms: -4 + 9y + -8y = 5 Combine like terms: 9y + -8y = 1y -4 + 1y = 5 Solving -4 + 1y = 5 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 1y = 5 + 4 Combine like terms: -4 + 4 = 0 0 + 1y = 5 + 4 1y = 5 + 4 Combine like terms: 5 + 4 = 9 1y = 9 Divide each side by '1'. y = 9 Simplifying y = 9
| -5x(x+7)=-5x+35 | | 2(7-14)=x-4 | | 5h-3(h+5)=5h | | -2+9+n=-4+6 | | t^2+8-9= | | -3(2x+3)+(7x-4)=0 | | -19+3+m=-3+17 | | -3n=18 | | x+25=-5 | | 2z/(2z-3)-3z/(2z+3)=(15-32z^2)/(4z^2-9) | | -4+7x+5=8(x+1)-5 | | x-48=19 | | 1.5n=-21 | | 5a-3+4a+5= | | 5.5x-5.3-5.7x=-1.2x-4.2 | | -28+x=x/7+2 | | 4p-5(p-2)=11 | | (y-5)(y-2)= | | 11=m-9 | | 3(x+1)=51 | | t^2-15+50= | | 3+7=37 | | y=-20+0.75x | | 2x+3x-9=0 | | 3(3-m)=1-m | | 3/(x+5)-(x-1)/(2x)=-3/(2x^2+10x) | | 2a-5=9 | | -4+6m+3=-4m-43-4m | | n+67=81 | | -16t^2+12t+8-10= | | 14y-20=10 | | 4/5(25x-15)=50x+38 |